The Severity of Covid-19 Infection and Vaccine Side Effects among the Saudi Population: Pharmaceutical Science-Pharmacology - Alhusseini, Noara; Ismail, Aya; A. Alaswad, Hani; Abodahab, Fawzy; Almutahhar, Shahad; S. Khader, Majd; Ramadan, Majed; Alabadi-Bierman, Alaa; M. Shakir, Ismail (International Journal of Life Science and Pharma Research, 2022)
COVID-19 first emerged in late 2019 in Wuhan, a city in the Hubie Province of China. Typical COVID-19 symptoms include fever, shortness of breath, and cough, whereas less common symptoms involve sudden onset of ageusia and/or anosmia, diarrhea, nausea, and vomiting. The primary objective was to compare the severity of symptoms among individuals infected with COVID-19 who have been vaccinated and those who have not. The second objective is to describe individuals’ post-vaccination side effects and complaints to understand Saudis’ aversion to vaccinations. This is a cross-sectional study among residents of Saudi Arabia including Saudis and non-Saudis. An online questionnaire was distributed via several social media channels. Univariate analysis was used to compare respondents’ demographic, COVID-19 infection, and post-vaccination characteristics. Bivariate associations were assessed using Chi-square . Adjacent categories logit model was used to compare severity reported levels and COVID-19 related and demographic factors. A total of 1,432 respondents completed the survey. Most of the infected individuals were not immune at the time of infection and reported more than four symptoms. There was no significant association between vaccinated and non-vaccinated individuals in terms of reporting COVID-19 severe infection. On the other hand, there were several significant predictors of reporting severe COVID-19 infection level as number of symptoms, hospitalization, gender, marital status, and education attainment. Men are more likely to report severe COVID-19 complications. Participants who hold a higher degree are more likely to report severe COVID-19 infection. Local side effects included pain, swelling, itchiness, warmth, and bruising at the site of the injection. Systemic side effects included fever, headache, fatigue, period changes, and diarrhea. Allergic side effects include local rash, skin burning, and urticaria. Further research is needed to better understand the severity and sideeffects of COVID-19 vaccines and even boosters.